Parents' Motivation for Choosing a Faith-Based School at Al-Azhar Islamic Elementary School, Cirebon City - Setia Budiyanti; Sugeng Muslimin; Turini Erawati (Ilmu Inovasi Nusantara, 2022)
Basic education as the beginning of compulsory education implemented by the government has become a difficult choice for parents to choose elementary schools in the midst of the times. Some parents hope that their children have good abilities and morals. This study aims to determine the factors that influence the motivation of parents to choose Islamic elementary schools at SD al-Azhar, Cirebon City. The study population was the guardian parents of grade 1 students and the study sample numbered 40 people. The research method is a survey method using a questionnaire instrument. The analysis technique used is descriptive with a quantitative approach. The results showed that the average score of the questionnaire was 146. The motivation of parents to choose al-Azhar Islamic Elementary School for their children has a variety of factors including facilities, curriculum, services, location, portion of religious education, quality of educators (teachers), environment and family, achievements and success of alumni. The main most dominant factors are the profile of educators (teachers) and school facilities (facilities and infrastructure).